A CONCEPTUAL FRAMEWORK OF RADICALIZATION AND VIOLENT EXTREMISM (Annual of the Faculty of Philosophy in Skopje, 2022)
Over the past decade, radicalisation has occurred as perhaps the most persistent conceptual framework for understanding micro-level modifications towards violence. Violent extremism and terrorism could be argued to be a function of society –as much as it is a reality of extremist groups or individuals who engage in violence due to ideological motivations. Radicalizing by evolving or embracing extremist beliefs that justify violence is one possible pathway into terrorism involvement, but it is certainly not the only one. Informed policies and practices to mitigate and prevent the spread of violent extremism require an understanding of these kinds of variations, not just general trends. The analysis of narratives used by the current radical and violent extremist groups’ shows that socio-economic, political and personal grievances are effectively used to sway public opinion, disseminate messages, gain new recruits, and elicit sympathy. These narratives are generally merged with characteristic terms imbedded in issues of political instability, socio-economic stagnation, civic strife, and, in some cases, war. The purpose of this paper is to clearly understand the relationship between these terms, so that the prevention of violence and/or the threat of violence can be more successful.
Keywords: radicalization; extremism; terrorism; violence; resilience